Late stent collapse in aortic coarctation—An interplay of residual pressure gradient and radial strength - Mahim Saran; Bijulal Sasidharan; Sivasankaran Sivasubramonian (IHJ Cardiovascular Case Reports, 2017)
A 50 year old male presented with uncontrolled hypertension and was diagnosed as coarctation of aorta. A covered stent was placed at the coarcted segment which collapsed after 3 months. We discuss the mechanism of this rare complication.